FSTI recognises excellent students - Nor Salwana, Mohammad Idris (2020)
KUANTAN, 11 December 2020 - The COVID-19 pandemic has not stopped the Faculty of Industrial Sciences and Technology (FSTI), Universiti Malaysia Pahang (UMP) from celebrating 451 excellent students during the Dean’s Award and Student Excellence Ceremony 2020 that was held online via Google Meet recently.